Relevansi Kerja Sama Regional dan Global terhadap Upaya Penanganan Pandemi COVID-19 - Pandjaitan XIV, Qanszelir GB; Tular, Axel Gabriel; Khonery, Clarissa; Leonora, Gracella; Then, Josephine Alessia; Suwarto, Nicholas Peter Sebastian (Global and Policy Journal of International Relations, 2022)
ABSTRACTCOVID-19 pandemic has been the main focus and topic of discussion for the last few years. Almostevery country were hit by the fear of it and rushed by the maximum efforts of holding on whilerecovering themselves from the crises of health, social, economy, and politics. There are real needs ofglobal cooperative responses in order to deal with this kind of situation. The role of internationalcooperation is highly crucial in dealing with the pandemic. It will promote researchers to conductstudies dedicated to prove the relevancy of the role of international organization and globalcooperation, describing the contributions, explaining the obstacles, and finally offering the potentialsolutions to handle the COVID-19 pandemic. This research uses the online searching method byanalysing data from the online media. Result of the analysis shows that although there are some realcollective efforts from various regional and global cooperation resulted in positive outcomes in somecountries, there are some obstacles and challenges left caused by lack of cooperative spirit from fewcountries. Those countries have not maximize their contribution to the international cooperation andorganization in dealing with the COVID-19 pandemic. Therefore, hopefully this research couldpromote the improvement of the international cooperation, either in regional or global scale, soevery countries will be able to get through the COVID-19 pandemic.Keywords: COVID-19, Regional Cooperation, Global Cooperation, Online SearchingDOI: https://doi.org/10.33005/jgp.v10i01.3577